2013
DOI: 10.1144/petgeo2011-043
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology and stratigraphy of an intra-cratonic basin coal seam gas play: Walloon Subgroup of the Surat Basin, eastern Australia

Abstract: Large gas reserves are trapped in the coals of the Middle Jurassic (Callovian) Walloon Subgroup (lower part of the Injure Creek Group) in the Surat Basin, eastern Australia. The series is divided into the Juandah Coal Measures (upper), Tangalooma Sandstone and Taroom Coal Measures (lower).The upper and lower units are locally further subdivided. These economically important coals were deposited in an alluvial plain setting within an interior basin, which has no recorded contemporaneous marine influence. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Results of basin and maceral analysis (D. Pacey, unpubl. data;Hamilton et al, 2014b; this paper), as well as chemo-and biostratigraphy (Martin et al, 2013) imply a maximum flooding surface (MFS) in the Lower Juandah Coal Measures, which marks a transition from deepening-to shallowing-up strata. Above this MFS, progressive 13 C-enrichment of the coals is interpreted to reflect changing climatic and depositional conditions (increasing aridity and/or water table fluctuation).…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 2 more Smart Citations
“…Results of basin and maceral analysis (D. Pacey, unpubl. data;Hamilton et al, 2014b; this paper), as well as chemo-and biostratigraphy (Martin et al, 2013) imply a maximum flooding surface (MFS) in the Lower Juandah Coal Measures, which marks a transition from deepening-to shallowing-up strata. Above this MFS, progressive 13 C-enrichment of the coals is interpreted to reflect changing climatic and depositional conditions (increasing aridity and/or water table fluctuation).…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Recent studies of coal geometry (Ryan et al, 2012;Sliwa and Esterle, 2008) and vertical lithofacies associations Martin et al, 2013) identified significant variation…”
Section: Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The depositional facies of the Wenchang Formation were analysed under a second‐order sequence stratigraphic framework (Martin, Wakefield, Macphail, Pearce, & Edwards, ; Shao, ; Wu, Hu, Liu, Zhang, & Yin, ; Zhu et al, ). In the Eocene, the main depositional facies are middle–deep lacustrine facies, shallow lacustrine facies, and delta and fan delta facies (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…CSG development areas are reasonably shallow at 100-1000m below ground level and produce from moderate rank, sub-bituminous coals. The gross zone of commercial interest is typically 300-450m thick (Martin et al 2013) and comprises 10% net coal (~30m in total). Coal seams are generally thin (mean thickness: 30cm) and are interbedded with low permeability clastic rocks.…”
Section: Walloon Coal Measuresmentioning
confidence: 99%